Em questão o sentido da docência - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Inserted in the research line Culture, School, and Formation of the Graduate Program in Education at the State University of Goiás (PPGE-UEG/Inhumas), the theoretical research titled In Question: the Concept of Teaching was carried out through the exercise of philosophical reflection based on a bibliographic selection relevant to the theme investigated. The study, aiming to reflect on teaching in the present day, brings to memory the genesis of the University as well as the movement of deviation and distancing from its origin, meaning, and purposes. Considering the selection of authors and works such as Chauí (1986, 2001, 2003), Coêlho (1986, 2011, 2012, 2016), Cunha (2000), Franco (1998), Ullmann and Bohnen (1994), Verger (1999), Adorno and Horkheimer (1985), Horkheimer (2015), Fernandes (2010, 2014, 2016, 2024), Nunes (1978 and 2006), among others, the aim was to think about the concept of teaching, especially from the work of Ildeu Moreira Coêlho, an author who has devoted more than half a century to studying the constitutive issues of human formation and teaching. The reflection resulting from the research was explained in three (3) chapters: Chapter 1 – The Genesis of the University: the Concept of Teaching; Chapter 2 – Reflections on Modernity: Teaching in the Context of Instrumentality (or Instrumental Reason); Chapter 3 – The Meaning of Teaching: Questions on Human Formation, followed by the Final Considerations. Based on the study conducted, it is possible to infer that, in capitalist society, the University and teaching, entangled by instrumental reason, by the pursuit of market demands, and by other factors, have distanced themselves from their origin and meaning. Recognizing such distancing is fundamental, but not sufficient when what is considered urgent and essential is a rupture with what is instituted in the field of education and formation. It is necessary to strive to think and carry out teaching oriented by what constitutes it and makes it truly what it is.
The question is the meaning of teaching
Keywords: Univerisidade; Formação humana; Professor; University; Teacher; Human formation; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO